Unraveling Financial Fraud: The Role of the Board of Directors and External Advisors in Conducting Independent Internal Investigations* - Files, Rebecca; Liu, Michelle (Contemporary Accounting Research, 2022)
ABSTRACT Although firms are encouraged by the SEC and Department of Justice to conduct internal investigations following financial misconduct, prior research finds few benefits for investigating firms. This study examines a novel aspect of internal investigations—namely, whether the investigation is conducted by independent versus nonindependent teams—and explores the impact of these teams on investigation outcomes. Consistent with our predictions, we find that firms whose internal investigations are led by independent teams are more likely to retain external advisors, have a higher likelihood of CEO turnover, and face a lower likelihood of an SEC enforcement action than do firms whose investigations are led by nonindependent teams. Our findings demonstrate that the SEC grants enforcement leniency to firms that conduct an internal investigation, but this finding only holds when the investigation leader is considered independent. These results also suggest that appointing independent groups to lead internal investigations protects the firm, at the expense of the CEO, following accounting fraud. Our paper has important implications for researchers studying accounting irregularities as we are the first to show that independent board members and external advisors play a direct role in the resolution of financial misconduct through their job on the internal investigation team.